A Case Report of Splenic Tuberculous Abscess - Sah, Manoj Kumar; Thapa, Bhawesh; Shrestha, Samrat (Journal of Advances in Internal Medicine, 2018)
Tuberculosis is a common infectious disease in South-Asian region which can involve different organs. Splenic tuberculosis is a rare clinical entity. Here we report a case of tuberculous abscess of spleen in a 72 year old diabetic male. It was disseminated type, it was confirmed by ultrasonography guided aspiration of abscess for gene x-pert test, which was positive. Patient was given antitubercular treatment after the confirmation of the diagnosis and is improving with given treatment.